Case Study Database - Moreno Beguerisse, Mariale; Charnley, Fiona; Court, Richard; Wright, Matt (Cranfield University, 2017)
Database of Case Studies Analysed;'Database of Case Studies Analysed'
Keywords: Circular Economy'; 'Case Study'; 'Re-distributed Manufacture'; 'Manufacturing Management'